PERENCANAAN SALURAN SEKUNDER D.I BATANG SOPAN KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Risma Leni; Deddy Kurniawan; Ana Susanti Yusman (Progressive Journal of Advanced Engineering and Technology, 2026)
Batang Sopan Irrigation Area is located in Village Batuang Country Simpang Timo Abu. The Batang Sopan irrigation area irrigates rice fields with an area of 107 ha, the water source comes from the Batang Sopan river 500 m from the settlement of Village Batuang residents, 44 km from Simpang Empat city center. In irrigation planning, analysis of rainfall data, cross-sectional shape, water discharge and channel dimensions is carried out so that the planned irrigation system is able to provide optimal and efficient water needs for community agricultural land so that agricultural output increases. The purpose of planning the Batang Sopan irrigation canal, Talamau District, West Pasaman Regency is to meet the water needs for local community rice fields in order to produce maximum and quality crops. In this irrigation canal planning, the channel dimensions are obtained from the calculation of rainfall data using the Haspers method and the Gumbel method based on 10-year maximum rainfall data from three rainfall stations. Calculations using the Gumbel method obtained a maximum rainfall of 4462 mm and the Haspers method obtained a discharge of 24.94 m3 / second. The channel type in the D.I Batang Sopan planning is trapezoidal in shape with a channel discharge of 34.77 m3 / second, so the planned channel dimensions can accommodate the discharge at the maximum discharge state.Keywords: Secondary channel, Gumbel method, Haspers method